Effects of fuel injection and energy efficiency on the production and environmental parameters of electric arc furnace -heat recovery systems. (15th June 2023) - Tian, Bohan; Wei, Guangsheng; Hu, Hang; Zhu, Rong; Bai, Hao; Wang, Ziming; Yang, Lingzhi
Abstract: A stoichiometric model of an electric arc furnace (EAF)-heat recovery system was constructed to display material, energy, and exergy behaviors, as well as production and environmental parameters, in order to study the effects of different fuel injection indexes. The injection of high-calorific value fuel (rather than hydrogen and biomass) reduces power consumption more effectively, but hydrogen utilization reduces the amount of off-gas and improves heat recovery slightly (0.06 MJ/Nm 3 ) in the case of 30% energy efficiency. It is more efficient to directly use the energy released from fuel combustion in the furnace than to recover the heat in the off-gas, showing the importance to increase energy efficiency. In the scenario of improved equipment and technology using large amounts of hydrogen (20 m 3 /t) and biomass (40 kg/t), power consumption will reach 322 kWh/t. Near-zero carbon emissions (41.20 kg CO2 /t) can be achieved in an EAF by using green power, green hydrogen, and advanced equipment and processes. However, realizing this process requires long-term transformation, including the use of coke oven gas rather than gray hydrogen, which has high upstream emissions. Moreover, there is a significant exergy loss in the off-gas heat recovery system (>70%), which requires the adoption of stoichiometric combustion and an increase in the efficiency of heat exchange.